2020
DOI: 10.1039/d0cp00943a
|View full text |Cite
|
Sign up to set email alerts
|

Si2BN monolayers as promising candidates for hydrogen storage

Abstract: The Si2BN monolayer is predicted to be a promising candidate for molecular hydrogen storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The average binding energies of absorbed H 2 molecules with van der Waals correction is −0.412 eV and its corresponding desorption temperature is 305 K, calculated with the following van't Hoff equation. 98–100 where T d , E b , k B , P , R , and Δ S are desorption temperature, adsorption energy, Boltzmann constant, ambient pressure, gas constant, and change in entropy for H 2 molecules going from gas phase to liquid phase (130.68 J K −1 mol −1 101 ), respectively. The strongly (−0.53 eV) and weakly (−0.27 eV) attached hydrogen molecules set the maximum and minimum limit of desorption temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The average binding energies of absorbed H 2 molecules with van der Waals correction is −0.412 eV and its corresponding desorption temperature is 305 K, calculated with the following van't Hoff equation. 98–100 where T d , E b , k B , P , R , and Δ S are desorption temperature, adsorption energy, Boltzmann constant, ambient pressure, gas constant, and change in entropy for H 2 molecules going from gas phase to liquid phase (130.68 J K −1 mol −1 101 ), respectively. The strongly (−0.53 eV) and weakly (−0.27 eV) attached hydrogen molecules set the maximum and minimum limit of desorption temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these analyses, it may be concluded that these three molecules are all physisorbed on the diazine monolayer. To clarify the physisorption of molecules on the monolayer, we also investigated the electron localization function (ELF), which is an efficient method to understand the features of chemical bonding, the lone electron pairs (nonbonding electron pairs), and (non)­covalent interactions between the molecules and the monolayer, and the results of the analysis of the characteristics of chemical bonding for the molecule adsorption system are similar to those of the noncovalent interactions analysis. , The ELF function has values between 0 and 1, which represents delocalization and the perfect localization features of the covalent bonding or the lone electron pairs, respectively. The ELF plots for the adsorption of the considered three molecules are presented in Figure a–c.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its exceptional structure and properties, the Si 2 BN-ML exhibits prospective applications beyond those of graphenes, and it has generated ample interest among the scientific community. Studies reported that the Si 2 BN-ML is suitable for the anode applications of Li-ion, Na-ion and Mg-ion batteries, 27,28 hydrogen storage, 29,30 etc. In 2018, by employing time-dependent density functional theory (TDDFT) calculations, Yuan et al investigated the optoelectronic and photosensitive detector applications of Si 2 BN nanostructures and their hybrids.…”
Section: Introductionmentioning
confidence: 99%